Kenabian dan Prognose Historis: Tinjauan atas Tulisan-Tulisan Romo van Lith - Rosariyanto, Fl. Hasto (Jurnal Orientasi Baru, 2012)
Though as a film, SOEGIJA was primarily thought as a Catholic film, it has actually another important theme, namely, nationalism. This writing sought to show that the involvement of the Catholic Church in the national struggle has actually a long history. It goes back to a well-known Dutch missionary called Rev. F. van Lith, SJ. In his time, he proposed a different strategy of doing missionary work. Instead of baptizing, he chose a completely different approach, namely, cultural approach. His choice was based on his respect to indigenous culture. And in turn, it shaped his political vision as well. A missionary Church must be in the part of local people, less she would find difficulties. Three key words should be mentioned here: independent, involvement and liberation.